Molecular Docking Senyawa Bioaktif Ekstrak Daun Cantigi (Vaccinium varingiaefolium (Blume) Leaves) pada Enzim COX-2 sebagai Anti-Inflamasi - Salsa Yosrika Putri; Fitri Amelia (Lembaga Yasin AlSys, 2026)
The use of natural products as anti-inflammatory agents is becoming increasingly important due to the long-term side effects of synthetic drugs. Cantigi (Vaccinium varingiaefolium), an Indonesian mountain plant species, is known to contain various bioactive compounds. This study aimed to explore the potential of compounds from cantigi leaves as COX-2 enzyme inhibitors using a molecular docking approach. A total of 19 compounds were examined through Lipinski screening, ADMET prediction, and docking against COX-2 (PDB: 6COX). The results showed that eight compounds met all Lipinski parameters and thus have potential to be developed as oral drug candidates, while ADMET analysis indicated that α-bisabolol and 2H-tetrazole possess favorable absorption and distribution profiles with minimal toxicity. Molecular docking analysis revealed that ligand 14 exhibited the highest binding energy (ΔG = –7.8262 kcal/mol) and interacted with the His386 residue, the same binding site as indomethacin, thereby suggesting a potentially similar mechanism of action. This study concludes that several compounds from cantigi leaves have promising potential as natural anti-inflammatory agents. These findings contribute to the development of local phytopharmaceuticals based on computational evidence and provide a foundation for further experimental research in the development of effective and safe herbal medicines.